2018
DOI: 10.1016/j.pestbp.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Quinclorac resistance induced by the suppression of the expression of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase and ACC oxidase genes in Echinochloa crus-galli var. zelayensis

Abstract: We previously reported that the mechanism of quinclorac resistance in Echinochloa crus-galli var. zelayensis may be closely related to ethylene biosynthesis and the detoxification of cyanide. Differences in EcCAS gene sequences and expression levels may result in higher capacity to detoxify cyanide in resistant biotypes, which may avoid cyanide accumulation and avoid more ethylene and cyanide production and then avoid damage. In the present study, we focused on the mechanism of resistance related to ethylene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
6
29
0
Order By: Relevance
“…In addition, previous report showed that both IAA and ACC-deaminase can stimulate plant root elongation [45]. Similarly, Gao et al (2018) reported that the species of Pseudomonas putida and T. atroviride can modulate the regulation of IAA and ethylene in the rhizosphere and within the roots to promote the development of the root system and of the tomato ( Solanum lycopersicum ) plant by their ability to produce and degrade IAA, and ACC-deaminase activity in general [46]. Grave et al (2007) found that the phytohormone of IAA produced by the microbes that can modulate the synthesis of plant ethylene, such as inhibits the transformation of ACC into ethylene by decreasing the activity of ACO [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous report showed that both IAA and ACC-deaminase can stimulate plant root elongation [45]. Similarly, Gao et al (2018) reported that the species of Pseudomonas putida and T. atroviride can modulate the regulation of IAA and ethylene in the rhizosphere and within the roots to promote the development of the root system and of the tomato ( Solanum lycopersicum ) plant by their ability to produce and degrade IAA, and ACC-deaminase activity in general [46]. Grave et al (2007) found that the phytohormone of IAA produced by the microbes that can modulate the synthesis of plant ethylene, such as inhibits the transformation of ACC into ethylene by decreasing the activity of ACO [47].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was performed using a SYBR Premix Ex Taq kit (Takara Biotechnology, Dalian, China) following the manufacturer′s instruction. Specific primer for each gene ( TaTGW6 , TaIAGLU , TaACO , TaACO1 , TaACO2 , TaACS , TaACS1 , TaACS7 , SOS1 and Actin genes) was designed according to the EST sequences of wheat in NCBI [46, 65, 71] using Primer Express 5.0 software that amplifies the target genes (Table 2). The Actin gene of wheat was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…This result is generally consistent with previous studies. 26,27,43 Lower levels of inducible expression of ACS and ACO genes in quinclorac-resistant E. crus-pavonis and other species indicates that upstream auxin signal reception/ transduction in QR1 is not as efficient as in QS plants, and hence likely results in lower ethylene productionin QR1. Measurement of ACS and ACO activities as well as ethylene levels in QR versus QS plants will provide further evidence.…”
Section: Discussionmentioning
confidence: 99%
“…mitis. [25][26][27] Higher basal levels of gene expression and/or activity of the HCN detoxifying enzyme ⊎-cyanoalanine synthase (⊎-CAS) were also found in resistant versus susceptible plants in weedy species like Digitaria ischaemum, E. phyllopogon, E. crus-galli var. zelayensis, and E. crus-galli var.…”
Section: Introductionmentioning
confidence: 99%
“…It not only generates differential genes, but also the functional molecular markers like simple sequence repeats (SSRs) and SNPs in various minor millet species. Enormous transcript profiles have been developed in weedy Echinochloa species till date for various traits associated with invasiveness and adaptations such as herbicide resistance, photosynthesis, flooding response, and other homeobox genes (Li et al, 2013a,b;Yang et al, 2013;Nah et al, 2015;Xu et al, 2015;Guo et al, 2017;Gao et al, 2018). Recently, transcriptome sequences developed from cultivated E. frumentacea variety CO (Kv) 2, yielded 97,065 transcripts with an average length of 94 Mbp (Murukarthick et al, 2019).…”
Section: Transcriptome Analysismentioning
confidence: 99%